Final results from PRIME: randomized phase III study of panitumumab with FOLFOX4 for first-line treatment of metastatic colorectal cancer - Douillard, J Y; Siena, S; Cassidy, J; Tabernero, J; Burkes, R; Barugel, M; Humblet, Y; Bodoky, G; Cunningham, D; Jassem, J; Rivera, F; Kocákova, I; et al. (Annals of oncology, 2014)
BACKGROUND: The Panitumumab Randomized trial In combination with chemotherapy for Metastatic colorectal cancer to determine Efficacy (PRIME) demonstrated that panitumumab-FOLFOX4 significantly improved progression-free survival (PFS) versus FOLFOX4 as first-line treatment of wild-type (WT) KRAS metastatic colorectal cancer (mCRC), the primary end point of the study. PATIENTS AND METHODS: Patients were randomized 1:1 to panitumumab 6.0 mg/kg every 2 weeks + FOLFOX4 (arm 1) or FOLFOX4 (arm 2). This prespecified final descriptive analysis of efficacy and safety was planned for 30 months after the last patient was enrolled. RESULTS: A total of 1183 patients were randomized. Median PFS for WT KRAS mCRC was 10.0 months [95% confidence interval (CI) 9.3-11.4 months] for arm 1 and 8.6 months (95% CI 7.5-9.5 months) for arm 2; hazard ratio (HR) = 0.80; 95% CI 0.67-0.95; P = 0.01. Median overall survival (OS) for WT KRAS mCRC was 23.9 months (95% CI 20.3-27.7 months) for arm 1 and 19.7 months (95% CI 17.6-22.7 months) for arm 2; HR = 0.88; 95% CI 0.73-1.06; P = 0.17 (68% OS events). An exploratory analysis of updated survival (>80% OS events) was carried out which demonstrated improvement in OS; HR = 0.83; 95% CI 0.70-0.98; P = 0.03 for WT KRAS mCRC. The adverse event profile was consistent with the primary analysis. CONCLUSIONS: In WT KRAS mCRC, PFS was improved, objective response was higher, and there was a trend toward improved OS with panitumumab-FOLFOX4, with significant improvement in OS observed in an updated analysis of survival in patients with WT KRAS mCRC treated with panitumumab + FOLFOX4 versus FOLFOX4 alone (P = 0.03). These data support a positive benefit-risk profile for panitumumab-FOLFOX4 for patients with previously untreated WT KRAS mCRC. KRAS testing is critical to select appropriate patients for treatment with panitumumab.
Keywords: geny ras; Genes, ras; Humans; fluoruracil; lidé středního věku; metastatic colorectal cancer; Leucovorin; Quality of Life; Panitumumab; Antibodies, Monoclonal; Aged; Female; dospělí; protokoly protinádorové kombinované chemoterapie; senioři; lidé; leukovorin; kvalita života; Adult; Neoplasm Metastasis; metastázy nádorů; antibody; ženské pohlaví; kolorektální nádory; Male; Middle Aged; panitumumab; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; Fluorouracil; monoklonální protilátky; chemotherapy; senioři nad 80 let; organoplatinové sloučeniny; FOLFOX; mužské pohlaví; Organoplatinum Compounds; Colorectal Neoplasms